Targeting non-coding RNAs to overcome osimertinib resistance in EGFR-mutated non-small cell lung cancer - Zeng, Beilei; Gan, Kelun; Yu, Yuanhang; Hu, Jianping; Deng, Qiao; Yin, Chong; Gao, Xi (Frontiers in Oncology, 2024)
Osimertinib, a third-generation inhibitor of epidermal growth factor receptor (EGFR) tyrosine kinase, exhibits remarkable efficacy in prolonging the survival of patients with non-small cell lung cancer (NSCLC) carrying EGFR mutations, surpassing the efficacy of first- and second-generation EGFR tyrosine kinases. Nevertheless, the emergence of osimertinib resistance is inevitable, necessitating an investigation into the underlying mechanisms. Increasing evidence has revealed that non-coding RNAs (ncRNAs), including microRNAs, long ncRNAs, and circular RNAs, play a significant role in the development and progression of lung cancer. These ncRNAs regulate essential signaling pathways, offering a novel avenue for understanding the fundamental mechanisms of osimertinib resistance. Recent studies have reported the significant impact of ncRNAs on osimertinib resistance, achieved through various mechanisms that modulate treatment sensitivity. We provide a concise overview of the functions and underlying mechanisms of extensively researched ncRNAs in the development of osimertinib resistance and emphasize their potential clinical application in EGFR-mutated NSCLC resistant to osimertinib. Finally, we discuss the obstacles that must be addressed to effectively translate ncRNA-based approaches into clinical practice.